Fabrication of 3D printed objects with controlled surface chemistry and topography. (January 2018) - Vargas-Alfredo, Nelson; Reinecke, Helmut; Gallardo, Alberto; del Campo, Adolfo; Rodríguez-Hernández, Juan
Graphical abstract: Highlights: 3D objects with controlled functionality and microstructure were fabricated. 3D structures were topographically modified by means of the Breath Figures approach. Wet chemical modification allowed us, in turn, to finely tune the surface composition. The chlorsulphonation methodology permitted a precise control over density of the surface functional groups. Abstract: We describe a novel strategy to modify the surface topography as well as the chemical composition of 3D parts fabricated by additive manufacturing. The 3D objects were fabricated by fused deposition modeling (FDM) using styrene filaments. The surface of the objects was then topographically modified providing materials with porous surfaces by means of the Breath Figures approach. By immersion of the object in a chloroform/polystyrene solution during few seconds and evaporation in a controlled humidity chamber, 3D objects decorated with pores over the entire surfaces could be prepared. Moreover, this approach permitted the modification of the pore size as a function of the immersion time as well as the solution concentration. Finally, the porous surface was modified by using a chemical treatment with chlorosulfonic acid. The created chlorosulfonyl groups were used to anchor different chemical compounds to the 3D object with the subsequent change of their surface properties.